2009
DOI: 10.1002/hup.1068
|View full text |Cite
|
Sign up to set email alerts
|

Opioid use affects antioxidant activity and purine metabolism: preliminary results

Abstract: Objective More must be learned about metabolic and biochemical alterations that contribute to the development and expression of drug dependence. Experimental opioid administration influences mechanisms and indices of oxidative stress, such as antioxidant compounds and purine metabolism. We examined perturbations of neurotransmitter-related pathways in opioid dependence (OD). Methods In this preliminary study, we used a targeted metabolomics platform to explore whether biochemical changes were associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 65 publications
2
40
0
Order By: Relevance
“…By complementing the more targeted approaches that have looked at one or few biochemical events at a time, it promises to provide a detailed map of the regulation of metabolic pathways as influenced by genome and environment (12, 13). We and others have reported initial metabolomic signatures for several disease states, including motor neuron disease, schizophrenia, depression, addictive disorders, Parkinson's disease, Huntington's disease, cardiovascular disorders and diabetes (1524). However, to date, no study has used a systems biochemistry approach to evaluate multiple metabolomic changes in an autopsy confirmed sample of AD and control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…By complementing the more targeted approaches that have looked at one or few biochemical events at a time, it promises to provide a detailed map of the regulation of metabolic pathways as influenced by genome and environment (12, 13). We and others have reported initial metabolomic signatures for several disease states, including motor neuron disease, schizophrenia, depression, addictive disorders, Parkinson's disease, Huntington's disease, cardiovascular disorders and diabetes (1524). However, to date, no study has used a systems biochemistry approach to evaluate multiple metabolomic changes in an autopsy confirmed sample of AD and control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Besides direct/exposure metabolites, methadone can also induce biochemical alterations, which may be of major interest in understanding potential toxic effects (Deng et al, 2012;Dinis-Oliveira, 2014b;Jiang et al, 2003;Mannelli et al, 2009). Indeed, patients undergoing methadone treatment showed altered oxidation-reduction activity confirmed by higher plasma levels of a-and c-tocopherol and increased GSH/GSSG ratio, and altered purine metabolism evidenced by increased concentration of guanine and xanthosine, with decreased guanosine, hypoxanthine and hypoxanthine/xanthine and xanthine/xanthosine ratios (Mannelli et al, 2009).…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Indeed, patients undergoing methadone treatment showed altered oxidation-reduction activity confirmed by higher plasma levels of a-and c-tocopherol and increased GSH/GSSG ratio, and altered purine metabolism evidenced by increased concentration of guanine and xanthosine, with decreased guanosine, hypoxanthine and hypoxanthine/xanthine and xanthine/xanthosine ratios (Mannelli et al, 2009). Nevertheless, these represent preliminary results and further studies are needed in this field to claim them as useful biomarkers of disease or response to methadone treatment.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Different concentrations of purine nucleotide (25 mg/ mL, 75 mg/mL, 125 mg/mL, 175 mg/mL, 225 mg/mL) were used for the experiment. Effects of purine nucleotide administration on purine nucleotide metabolism in brains of heroin-dependent rats 793 decreased GMP concentrations are associated with opioid dependence in humans (Mannelli et al, 2009). It has also been shown that opioid use may have toxic effects on the central and peripheral nervous systems, leading to irreversible, pathological cellular changes.…”
Section: Content Detection Of Purine Nucleotidesmentioning
confidence: 99%